If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.04 + -0.02(x + 1) = -0.03(1 + -1x) Reorder the terms: 0.04 + -0.02(1 + x) = -0.03(1 + -1x) 0.04 + (1 * -0.02 + x * -0.02) = -0.03(1 + -1x) 0.04 + (-0.02 + -0.02x) = -0.03(1 + -1x) Combine like terms: 0.04 + -0.02 = 0.02 0.02 + -0.02x = -0.03(1 + -1x) 0.02 + -0.02x = (1 * -0.03 + -1x * -0.03) 0.02 + -0.02x = (-0.03 + 0.03x) Solving 0.02 + -0.02x = -0.03 + 0.03x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03x' to each side of the equation. 0.02 + -0.02x + -0.03x = -0.03 + 0.03x + -0.03x Combine like terms: -0.02x + -0.03x = -0.05x 0.02 + -0.05x = -0.03 + 0.03x + -0.03x Combine like terms: 0.03x + -0.03x = 0.00 0.02 + -0.05x = -0.03 + 0.00 0.02 + -0.05x = -0.03 Add '-0.02' to each side of the equation. 0.02 + -0.02 + -0.05x = -0.03 + -0.02 Combine like terms: 0.02 + -0.02 = 0.00 0.00 + -0.05x = -0.03 + -0.02 -0.05x = -0.03 + -0.02 Combine like terms: -0.03 + -0.02 = -0.05 -0.05x = -0.05 Divide each side by '-0.05'. x = 1 Simplifying x = 1
| (x+3)(x-1)=2x | | t^2+8t-16=0 | | 4(3n+5)=7(6n+5)+9 | | 14p+16q+p-4q-4p= | | 17.5x=125 | | 18/s=33 | | 3(2y-1)-9= | | 7(3n+2)=8(6n+1)+9 | | 45*45=x | | 4a-2=3a-8 | | -14x-20=-11x+100 | | -4-(5-6p)= | | 2w+1=3w-2 | | 9x^2-45x+116=0 | | 4(2y+1)=8 | | (4y+3)/7=9 | | 9(3n+1)=7(9n+3)+9 | | 5(y+4)-35= | | 4(2n+1)=6(9n+2)+2 | | g-5/5=4/5 | | (X*0.365)+(X*.2)=100 | | 4x+5/8=5x+5/8 | | 9x-87=6x-9 | | 10-5(n+4)=11 | | -4(v+7)=7v+27 | | 6y+3(y-5)=4(y+1)-3 | | -4(4y-5)+2(2y+10)= | | Y-(1/2)=3/4 | | 0.8(0.1x+0.5)-0.8= | | 0.16(y-4)+0.08y=0.02y-0.2 | | (1+2j)=(1/12-5j) | | 32+112x-16x^2=0 |